2015
DOI: 10.1002/open.201500167
|View full text |Cite
|
Sign up to set email alerts
|

A Structurally‐Tunable 3‐Hydroxyflavone Motif for Visible Light‐Induced Carbon Monoxide‐Releasing Molecules (CORMs)

Abstract: Molecules that can be used to deliver a controlled amount of carbon monoxide (CO) have the potential to facilitate investigations into the roles of this gaseous molecule in biology and advance therapeutic treatments. This has led to the development of light-induced CO-releasing molecules (photoCORMs). A goal in this field of research is the development of molecules that exhibit a combination of controlled CO release, favorable biological properties (e.g., low toxicity and trackability in cells), and structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
185
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(198 citation statements)
references
References 48 publications
7
185
0
Order By: Relevance
“…29). 81 Carbon monoxide is released by this system when irradiated at 419 nm in the presence of oxygen, which labelling studies demonstrated is incorporated into the photoproduct. By adjusting the framework to give 49, CO release could be affected using light with wavelength >546 nm.…”
Section: Metal-free Photocormsmentioning
confidence: 92%
“…29). 81 Carbon monoxide is released by this system when irradiated at 419 nm in the presence of oxygen, which labelling studies demonstrated is incorporated into the photoproduct. By adjusting the framework to give 49, CO release could be affected using light with wavelength >546 nm.…”
Section: Metal-free Photocormsmentioning
confidence: 92%
“…This would require the development of “caged” CO for release at the appropriate time and rate. There have been recent efforts in developing metal-based CO-RMs (or CO-prodrugs), 17, 39-42 encapsulated CO-RMs, 43-46 photo-sensitive organic CO-RMs, 47-49 and organic CO-prodrugs that spontaneously release CO under physiological conditions. 50 In addition to normal delivery route challenges, there are some special factors related to CO-based therapeutics, all of which would affect the development of pharmaceutically acceptable forms of a CO-prodrug.…”
Section: Existing Co-delivery Methodsmentioning
confidence: 99%
“…By modifying the substituent on the 3-hydroxyflavone scaffold (Figure 5), the activation wavelength can be tuned from 419 to 546 nm. 49 For example, exposure of 13a to light (419 nm) in an aerobic organic or aqueous solution resulted in quantitative CO release (0.96 equiv) in 10 min. Further structural modifications afforded three new analogues 13b, 13c and 13d .…”
Section: Existing Co-delivery Methodsmentioning
confidence: 99%
“…In the pursuit of a trackable, biocompatible organic photoCORM, we have initiated investigations of bioinspired molecules having an extended 3‐hydroxyflavone motif ( 18 , Figure ) . This novel framework exhibits several advantageous features for the delivery of CO in biological environments.…”
Section: Fluorescence Trackable Metal‐free Co‐releasing Molecules or mentioning
confidence: 99%
“…The ∼580 nm emission can be easily monitored using the GFP channel settings on a fluorescence microscope (Figure ). Cell‐based studies using 18 have shown good cellular uptake, with the compound being successfully visualized in the cytosol of human lung adenocarcinoma cells (A549 cells) and human umbilical vein cells (HUVECs) ,. Compound 18 exhibits minimal or no toxicity in both cell lines and the CO release by‐product 19 is non‐toxic up to 100 μM.…”
Section: Fluorescence Trackable Metal‐free Co‐releasing Molecules or mentioning
confidence: 99%